A stated preference analysis of real time public transport information - Caulfield, Brian Owen (Trinity College (Dublin, Ireland). Department of Civil, Structural and Environmental Engineering, 2008)
This thesis reports the outcomes of a study conducted to ascertain the benefits derived from the use of real-time public transport information. The study focuses upon three areas of individuals preferences in relation to the use of real-time public transport information. The first area examined in the study asked respondents to choose between the following options for receiving real-time public transport information: the internet, via a mobile phone, a passenger information display and a call centre. The second aspect of the study investigated what type of information respondents required across three stages of a public transport trip, defined as: pre-trip planning from home to work, at-stop/station information and pre-trip planning from work returning home. The third area assessed how a series of explanatory and attitudinal variables impact upon the benefits derived from real-time public transport information.
Keywords: Civil Engineering, Ph.D.; Ph.D. Trinity College Dublin